Genetic regulation of serum IgA levels and susceptibility to common immune, infectious, kidney, and cardio-metabolic traits - Lili Liu; Atlas Khan; Elena Sanchez-Rodriguez; Francesca Zanoni; Yifu Li; Nicholas Steers; Olivia Balderes; Junying Zhang; Priya Krithivasan; Robert A. LeDesma; Clara Fischman; Scott J. Hebbring; et al. (Nature Communications, 2022)
Immunoglobulin A protects against infectious disease and contributes to autoimmune and inflammatory disorders. Here, the authors perform a genome-wide association study for serum IgA levels, identifying 20 genome-wide significant loci, providing new insights into the genetic regulation of IgA levels.